Virtual Reality-Based Counseling Innovation for Depression Therapy in the Patient Healing Process - Agus Aan Aan Jiwa Jiwa Permana (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2026)
Depression is a mental disorder that significantly affects patients’ quality of life and psychological well-being, necessitating innovative therapeutic approaches. This study focuses on the development of Virtual Reality (VR)-based Counseling Innovation, as VR technology offers immersive and interactive experiences that enhance patient engagement and support the healing process. The research employs the Rapid Application Development (RAD) method, which includes requirement identification, prototype design, system construction, and implementation. The VR therapy model incorporates a calming night environment with natural sounds and a daytime environment accompanied by instrumental music to facilitate relaxation and emotional recovery. Testing was conducted with 12 respondents to evaluate system usability and user interface/user experience (UI/UX), yielding a System Usability Scale (SUS) score of 82.08, indicating high acceptance. The results demonstrate that the VR counseling model provides an enjoyable and effective experience that supports patients’ emotional healing. These findings suggest that VR-based counseling can serve as an innovative alternative for depression therapy, offering a personalized, interactive, and adaptive approach. Furthermore, the study provides a foundation for integrating digital technologies into modern psychotherapy practices, highlighting the potential of VR to enhance therapeutic engagement and promote mental health recovery in a controlled, immersive environment.